Towards a Better Understanding of Beta Diversity: Deconstructing Composition Patterns of Saproxylic Beetles Breeding in Recently Burnt Boreal Forest - Azeria, Ermias T.; Ibarzabal, Jacques; Boucher, Jonathan; Hébert, Christian (IntechOpen, 2011)
None